Retinal detachment in England: database studies of trends over time and geographical variation. Issue 5 (19th November 2014) - Shah, Vishal; Hall, Nick; Goldacre, Michael J
Abstract : Aims: Retinal detachment (RD) is one of the most common of ophthalmic emergencies in the UK. Our aim was to study trends over time and regional variation in rates of RD in England. Methods: Hospital admission rates for RD were analysed using the Hospital In-Patient Enquiry, Hospital Episode Statistics and the Oxford record linkage study between 1968 and 2011. Record linkage was used, when possible, to distinguish between episodes of care and individual people. Results: Person-based rates from the 1960s to mid-1990s (only available in the Oxford data) were broadly stable. From 1999, the annual person-based rate increased significantly, from 13.4 in 1999 (13.1 to 13.8) to 15.4 in 2011 (15.1 to 15.7). Most, if not all, of the increase was an increase in people with diabetes mellitus. RD rates, comparing local authority (LA) areas, ranged from 10.3 (9.0 to 11.6) to 22.4 per 100 000 (19.9 to 25.1) over the period 1999–2011. The rate of RD by LA showed almost no association with social deprivation (r 2 =0.01) or with the proportion of people in each LA who were Black (r=0.04), Asian (r =−0.03) or born outside the UK (r=0.02). Conclusions: Admission rates seem to have increased in recent years. This increase is probably attributable to an increase in the prevalence of diabetes, and so an increase in RD associated with diabetes. Understanding trends over time, and geographical variation, in RD will help match capacity in retinal surgery with need for treatment of RD.